Effect of melatonin implants on spermatogenesis in the domestic cat (Felis silvestris catus) - Nuñez Favre, Romina de Los Angeles (2014)
The aim of this study was to assess the efficacy of subcutaneous melatonin implants to temporarily and reversibly suppress spermatogenesis in male cats. Tomcats (n = 8) were housed in a conditioned room with alternating long and short 2-month photoperiod cycles to maintain sperm production and quality. Animals were randomly assigned to one of the two treatments. Four animals received a subcutaneous melatonin implant (MEL, 18 mg; Syntex, Argentina), whereas the other four received a subcutaneous placebo implant (PLA, 0 mg; Syntex). Semen samples were collected by electroejaculation every 14 days for 252 days. Sperm parameters were evaluated in all ejaculates, and data were analyzed by ANOVA. Melatonin-implanted cats significantly decreased their sperm quality in all the parameters studied compared with the control group (MEL vs. PLA; least squares means ± SEM; motility, 71.3 ± 3.4 vs. 82.1 ± 3.6; velocity, 3.4 ± 0.1 vs. 4.6 ± 0.1; total sperm count, 2.6 ± 2.2 vs. 19.4 ± 3.3; acrosome integrity, 48.7 ± 5.6 vs. 62.8 ± 5.6; plasma membrane integrity, 52.2 ± 4.7 vs. 72.9 ± 5.5; normal sperm morphology, 45.8 ± 3.3 vs. 63.7 ± 3.4; P < 0.05). Conversely, volume and serum testosterone concentrations were similar in both groups (volume, 0.15 ± 0.02; serum testosterone concentrations, 1.1 ± 0.1; CV 18.9%; P > 0.05). At 91 ± 7 days after implant insertion, sperm motility decreased 38.5%, velocity 26.5%, total sperm count 82%, acrosome integrity 22%, plasma membrane integrity 30%, and normal sperm morphology decreased 32% of preimplant values. This effect was present until 120 ± 15 days after implant insertion. After that, seminal parameters started to increase and reached preimplant values at about 140 ± 7 days after implant insertion. Nevertheless, treated animals conserved the capacity to produce semen during the treatment period. In conclusion, a single subcutaneous melatonin implant effectively and reversibly reduced sperm production and quality in male domestic cats for approximately 120 ± 15 days without clinically detectable adverse effects.